Legenda Rasa Kecap Meliwis: Jejak Perjalanan Kuliner Pendamping 1932-2024 dan Potensinya Sebagai Sumber Belajar Sejarah di SMA - Rahayuni, Luh Sulistia; Tuty Maryati; Desak Made Oka Purnawati (Widya Winayata : Jurnal Pendidikan Sejarah, 2025)
This study aims to (1) analyze the history of the establishment and dynamics of the development of Meliwis Soy Sauce in Temukus Village, (2) describe the dynamics of development and production factors that support the sustainability of the Meliwis Soy Sauce Factory in Temukus Village, (3) analyze aspects of Meliwis Soy Sauce that have the potential as a source of learning history in high school. The location of the research was carried out in Temukus Village, using a qualitative descriptive approach that plays a role in heuristic studies (interviews, observations, document studies), internal and external criticism, interpretation and historiography. The results of this study show (1) the history of the establishment of the Meliwis Soy Sauce Factory in Temukus Village, Banjar District, Buleleng Regency, Bali in 1932, (2) the dynamics of development and production factors of the Meliwis Soy Sauce Factory in Temukus Village, Banjar District, Buleleng Regency, Bali in 1932, (3) aspects of the history of the Meliwis Soy Sauce Factory that have the potential as a source of learning history in high school because they have high historical value that can be linked to history learning phase E of the History material: Humans, Space and Time.